Modifying the Wettability of Nitramine Explosives using Anionic, Cationic and Nonionic Surfactants. Issue 10 (13th July 2017) - Doukkali, Mouhcine; Gauthier, Eric; Patel, Rajen B.; Stepanov, Victor; Hadim, Hamid
Abstract: Wetting behavior of energetic materials surface including cyclotrimethylene trinitramine (RDX), cyclotetramethylene tetranitramine (HMX) and hexanitrohexaazaisowurtzitane (CL‐20) using nonionic (Triton‐X), anionic (SDS), and cationic (TTAB) surfactants has been studied by contact angle tensiometry. Results show that TTAB more significantly reduces the contact angle and improves wettability as compared to SDS and Triton‐X. The liquid‐vapor surface tension γ l v was measured as a function of TTAB surfactant concentration in aqueous solutions and used to construct a Zisman plot to determine the critical surface tension of RDX, HMX and CL‐20. The results show that HMX displays the highest degree of wettability while RDX is most difficult to wet. The computed values of the work of spreading complement the previously discussed results where contact angle decreases with increasing surfactant concentration. They also indicate that RDX appears most impacted by the addition of TTAB surfactant. However, the addition of TTAB also has a significant impact on improving the wettability of HMX and CL‐20. This wettability study plays an important role in the formation of well‐wetted energetic surfaces needed for efficient wet milling, coating and granulation processes. Abstract :